Academic engagement in virtual and unprecedented contexts. Adaptability to change in the university environment - Rigo, Daiana Yamila (2022)
The COVID-19 pandemic prompted students and other educational agents to suddenly switch from traditional and familiar formats to largely improvised distance learning formats. In this framework, the study presented explored the academic commitment linked to the adaptation process that students developed throughout the COVID-19 pandemic, in terms of cognitive, affective, behavioral and agentic resources that they deployed in the face of learning in virtual and unprecedented educational contexts. Methodologically, it was exploratory-descriptive of a qualitative nature to investigate, based on brief narratives requested from 61 university students from Argentina, about their perceptions of academic commitment linked to adaptability during the two years of virtual study -2020 and 2021-. The results show that students deploy an interesting variety of digital resources to adapt to new and uncertain situations. Secondly, there is an outstanding stress towards digital resources, fatigue and a greater sense of academic disconnection, together with alternatives that are co-created from the personal and collaborative agency to organize new virtual learning communities. What was found motivates us to rethink the return to presence, to reflect on the university class as a hybrid environment where presence is complemented by the virtual and promotes the commitment of students.